KOMUNIKASI KULTURAL ISLAM DAN BUDAYA - M Alfin Fatikh; Wahyu Hendrik (Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Cultural communication between Islam and local culture gave rise to the acculturation of religious culture in one of the Islamic tomb complexes of the Majapahit kingdom era located in Trowulan, Mojokerto, East Java. The architecture of this tomb still holds elements from Hindu culture which are very different when compared to Islamic tombs in general. This study aims to determine the existence of cultural communication that occurs between Islam and local culture based on the architecture of the Troloyo tomb complex. This research is literature-based research and the history of Islamic development in the Majapahit area. This cultural communication is seen with a Jirat or Kijing located on top of the tomb with three piles based on faith, Islam, and Ihsan, the tombstone also uses an upright stone (menhir) with Arabic encryption with name and date. Cungkup is built with a variety in the form of a Joglo or temple which is believed to be a temple to store the ashes of the king, one of which is a form of respect for the king in ancient times.